An outbreak investigation of Burkholderia cepacia infections related with contaminated chlorhexidine mouthwash solution in a tertiary care center in Turkey - GÜL, FETHİ; ALTINKANAT GELMEZ, GÜLŞEN; BİLGİN, HÜSEYİN; CİNEL, İSMAİL HAKKI; KORTEN, VOLKAN (BMC, 2021)
Background: We report a nosocomial outbreak caused by Burkholderia cepacia that occurred among six patients admitted in the medical and surgical intensive care unit between 04 March 2019 and 02 April 2019 in Istanbul, Turkey. Methods: The outbreak investigation was launched on 11 March 2019 five days after the detection of B. cepacia in four different patients. We defined potential reservoirs and started environmental screening. We sampled the liquid solutions used in patient care activities. Pulse-field gel electrophoresis (PFGE) was performed to determine the genetic relatedness of environmental and patient samples. Results: Burkholderia cepacia was isolated in tracheal aspiration cultures of six patients. Three out of six patients developed healthcare-associated pneumoniae due to B. cepacia. Environmental cultures in the ICUs revealed B. cepacia growth in 2% chlorhexidine-gluconate mouthwash solution that been used in the colonized patients as well as in samples obtained from the unused products. PFGE revealed the patient and a specific batch of chlorhexidine mouthwash solution samples had a 96% similarity. Conclusion: Contamination of medical solutions used in critical patient care could cause outbreaks and should be detected early by infection control teams.
Keywords: Burkholderia cepacia; Outbreak; Intensive care unit; Chlorhexidine mouthwash; Ventilator-associated-pneumoniae; Healthcare associated infection; Contamination; Outbreak investigation; CRITERIA; COMPLEX